Environmental characteristics of older people attending physical medicine and rehabilitation outpatient clinics - Beyazova, Mehmet; Doğan, Asuman; Kutsal, Yeşim Gökçe; Karahan, Sevilay; Arslan, Şule; Gökkaya, Kutay Ordu; Toraman, Füsun; Dinçer, Nilay; Hizmetli, Sami; Şenel, Kazim; Yazgan, Pelin; Ortancil, Özgür; et al. (Central European journal of public health, 2020)
OBJECTIVE: A residential environment refers to the physical and social characteristics in a neighbourhood. The physical characteristics include interior housing qualities, exterior neighbourhood characteristics, and the accessibility of essential facilities and services outside the neighbourhood. Older adults especially may be vulnerable to the negative impacts of the residential environment. The aim of this study is to elucidate the problems ageing people face in their neighbourhoods, buildings and public areas. METHODS: The study group consisted of a total of 1,001 people over the age of 65 who were admitted to physical medicine and rehabilitation clinics in Turkey and consented to participate. A questionnaire covering demographic, social and environmental information was used. RESULTS: Of the study group, 58.6% was living in an apartment building, but only 23.6% of these buildings had an elevator, and the stairs were inconvenient in 46.7% of the buildings. Only 49% of the elderly people went for a walk regularly. The most frequent complaint about the hospitals, community health centres and other public areas was the inappropriate restroom conditions. Eighty-six percent of the study group were not members of an organization, a foundation or a group, and 73.6% did not have personal hobbies. CONCLUSIONS: The layouts of buildings and surroundings are inappropriate for older people, and the opportunities for them to participate in social activities are limited. Health and social programmes and governmental and local policies for older people are needed, and public awareness about this issue should be raised.
Keywords: Physical and Rehabilitation Medicine; Ambulatory Care Facilities; aged population; Aged; charakteristiky bydlení; Residence Characteristics; rehabilitační lékařství; Humans; senioři; lidé; Turecko; environment; social life; ambulantní zařízení; Turkey